Analisis Curah Hujan Sebagai Unsur Agroklimatologi Terhadap Produksi Tanam Ubi Jalar ( Ipmea Batalas L. ) Di Kabupaten Tapanuli Selatan - Syawaluddin; Imelda Sari Harahap; Ismail Saleh Simbolon (PT FORMOSA CENDEKIA GLOBAL, 2022)
Rain is a very important factor in the availability of water for planting. Farmers still use the traditional method in determining the planting schedule. The determination is considered less than optimal. This study aims to analyze rainfall on sweet potato production in South Tapanuli Regency based on rainfall data, and determine the relationship between rainfall and the suitability of sweet potato plants. The research method used is survey method and literature review. This type of research is a survey method with a correlation and descriptive approach to see the relationship between rainfall and sweet potatoes which is used with correlation. From this research, the results of correlation and regression analysis of the rainfall variable on the sweet potato productivity variable for the last 10 years obtained from the Central Statistics Agency of South Tapanuli Regency describe a weak positive effect.